PHOTO-EDITORS AND PARA-PHOTOJOURNALISTS ON TWITTER. THE COMMODIFICATION OF NETWORKED IMAGES - Runge, Evelyn (Animus. Revista Interamericana de Comunicação Midiática, 2021)
The microblogging service Twitter has gained importance as an exchange platform for news photos that, in collaboration with renowned media, might trigger immediate reactions from photo editors. Twitter conversations among photo editors and photo creators – produsers, citizen photojournalists, para-photojournalists – show that photo editors turn to (amateur) photographers to request permission to use their eyewitness material in journalistic publications. Reviewing the contested space of digital visual journalism between produsers, photo editors, and the commodification of networked images, I present three scenarios which exhibit how terms of use are negotiated online – hence publicly visible – between creators of Twitpics and editors of newspapers or photo agencies. The paper concludes with five results of the relation between photo editors and para-photojournalists on Twitter: fairness, efficiency, the value of digital images, effects of image sharing practices on visual journalism, and produsers’ daily media practices.